The Dichotomy between Family Law and Family Crises on Marriage Breakdown - Payne, Julien (Revue générale de droit, 1989)
The following analysis focuses on three crises of marriage breakdown: the emotional crisis; the economic crisis; and the parenting crisis. The response of lawyers and of legal processes to these three crises that so frequently interact with each other is examined with a view to providing a broader perspective of family conflict resolution.